Concise Reviews: Can Mesenchymal Stromal Cells Differentiate into Corneal Cells? A Systematic Review of Published Data. (March 2015) - Harkin, Damien G.; Foyn, Leanne; Bray, Laura J.; Sutherland, Allison J.; Li, Fiona J.; Cronin, Brendan G.
Abstract The majority of stem cell therapies for corneal repair are based upon the use of progenitor cells isolated from corneal tissue, but a growing body of literature suggests a role for mesenchymal stromal cells (MSC) isolated from noncorneal tissues. While the mechanism of MSC action seems likely to involve their immuno‐modulatory properties, claims have emerged of MSC transdifferentiation into corneal cells. Substantial differences in methodology and experimental outcomes, however, have prompted us to perform a systematic review of the published data. Key questions used in our analysis included: the choice of markers used to assess corneal cell phenotype, the techniques used to detect these markers, adequate reporting of controls, and tracking of MSC when studied in vivo. Our search of the literature revealed 28 papers published since 2006, with half appearing since 2012. MSC cultures established from bone marrow and adipose tissue have been best studied (22 papers). Critically, only 11 studies used appropriate markers of corneal cell phenotype, along with necessary controls. Ten out of these eleven papers, however, contained positive evidence of corneal cell marker expression by MSC. The clearest evidence is observed with respect to expression of markers for corneal stromal cells by MSC. In comparison, the evidence for MSC conversion into either corneal epithelial cells or corneal endothelial cells is often inconsistent or inconclusive. Our analysis clarifies this emerging body of literature and provides guidance for future studies of MSC differentiation within the cornea as well as other tissues. Stem Cells2015;33:785–791